2013
DOI: 10.1007/s11259-013-9583-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of oral administration of transgenic tobacco seeds against verocytotoxic Escherichia coli strain in piglets

Abstract: The use of transgenic plants as delivery system for antigenic proteins is attractive for its simplicity and increases likelihood for local immune response at sites of infection. The aim of this study was to evaluate the protective effect of oral administration of tobacco seeds, expressing the FedA, the major protein of the F18 adhesive fimbriae, and B subunit of verocytotoxin, against verocytotoxin-producing E. coli (VTEC) strain in piglets. Forty-three early weaned piglets, were randomly divided into 4 experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 31 publications
0
42
1
Order By: Relevance
“…The ban on antibiotic growth promoters (EU Reg. 1831 in livestock led to the study of alternative compounds 2014a), however it increased the use of some minerals as growth stimulants and to prevent enteric diseases in pigs.…”
Section: Mineral Nutrition In Livestockmentioning
confidence: 99%
“…The ban on antibiotic growth promoters (EU Reg. 1831 in livestock led to the study of alternative compounds 2014a), however it increased the use of some minerals as growth stimulants and to prevent enteric diseases in pigs.…”
Section: Mineral Nutrition In Livestockmentioning
confidence: 99%
“…In pig livestock, Enterotoxigenic E. coli (ETEC) is the most important pathotype causing both neonatal and post-weaning diarrhea (PWD), which are responsible for significant economic losses worldwide and are the most common reason for the prescription of antimicrobials in intensive systems [11,12]. The proliferation of ETEC strains in the gut and their pathogenicity can be influenced by the expression of fimbrial adhesins, which bind to specific receptor sites on small intestinal enterocytes enabling the bacteria to colonize the small intestine [13,14]. ETEC strains equipped with F4 and F18 adhesive fimbriae show a high virulence and are the most common serotypes isolated in animals affected by PWD [15].…”
Section: Introductionmentioning
confidence: 99%
“…ETEC strains equipped with F4 and F18 adhesive fimbriae show a high virulence and are the most common serotypes isolated in animals affected by PWD [15]. As an alternative to antibiotics, new compounds are urgently needed to control enteric diseases and PWD in pig livestock [14]. Tannins are suitable due to their valuable extra-nutritional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2019) reported higher average concentration of Zn and Cu in swine manure compared to cattle and sheep manure in China (1313.00, 514.70 mg/kg, respectively). Through the manure, a large number of metallic ions can be absorbed into the soil, thus interfering with the quality of cultivation or increasing soil pollution (Lopez-Alonso et al 2012;Jakubus et al 2013;Rossi et al 2013;Rossi, Dell'Orto et al 2014a;Gul et al 2015;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%